Menorrhagia in inherited bleeding disorders in Iraqi women - Yusra Ghiath Yaseen; Elaf Zuhair Hmeed; Nidal Karim Al Rahal; Baan Abdulatif Mtashar (Iraqi Journal of Hematology)
BACKGROUND: Menorrhagia, or excessive menstrual bleeding, is a common symptom in women with inherited bleeding disorders; they are conditions where the blood ability to clot is impaired. Some of the common bleeding disorders include von Willebrand disease (VWD), clotting factor deficiencies, and platelet function disorders. OBJECTIVE: To assess different types of inherited bleeding disorders in women with menorrhagia referred to the National Center of Hematology/Mustansiriyah University in Baghdad/Iraq. PATIENTS AND METHODS: A prospective study was carried out on 193 women who had experienced menorrhagia for a duration of 3 years, from 2020 to 2023. These women sought consultation at the National Centre of Hematology/Mustansiriyah University. All participants were diagnosed through various laboratory tests, including complete blood count, blood film, blood group and Rh, bleeding time, prothrombin time, activated partial thromboplastin time, fibrinogen level, factor assay, von Willebrand factor antigen using ELISA technique, ristocetin cofactor, and platelet function test. RESULTS: Out of the 193 women with menorrhagia who participated in this study, the majority of whom had an unidentified cause (36.3%), followed by VWD (30.1%) and platelet function disorders (21.2%). Other bleeding disorders ( thrombocytopenia and factors deficiencies) were 5.7% and 6.7%, respectively. Furthermore, the results showed that there was a significant difference in family history and consanguinity between patients with a hereditary bleeding disorder and nonhereditary bleeding disorder (P < 0.001). CONCLUSIONS: Fifty eight percent of females with Menorrhagia in this study have inherited bleeding disorders(IBDs), VWD, and thrombasthenia account for 51.3% are the most common causes of inherit bleeding disorder (IBD). Consanguineous marriage should be discouraged in Iraqi society to reduce such inherited diseases.